Monocytes show immunoregulatory capacity on CD4+ T cells in a human in‐vitro model of extracorporeal photopheresis. (22nd November 2018) - Wiese, F.; Reinhardt‐Heller, K.; Volz, M.; Gille, C.; Köstlin, N.; Billing, H.; Handgretinger, R.; Holzer, U.
Summary: Extracorporeal photopheresis (ECP) is a widely used immunomodulatory therapy for the treatment of various T cell‐mediated disorders such as cutaneous T cell lymphoma (CTCL), graft‐ versus ‐host disease (GvHD) or systemic sclerosis. Although clinical benefits of ECP are already well described, the underlying mechanism of action of ECP is not yet fully understood. Knowledge on the fate of CD14 + monocytes in the context of ECP is particularly limited and controversial. Here, we investigated the immunoregulatory function of ECP treated monocytes on T cells in an in‐vitro ECP model. We show that ECP‐treated monocytes significantly induce proinflammatory T cell types in co‐cultured T cells, while anti‐inflammatory T cells remain unaffected. Furthermore, we found significantly reduced proliferation rates of T cells after co‐culture with ECP‐treated monocytes. Both changes in interleukin secretion and proliferation were dependent on cell‐contact between monocytes and T cells. Interestingly, blocking interactions of programmed death ligand 1 (PD‐L1) to programmed death 1 (PD‐1) in the in‐vitro model led to a significant recovery of T cell proliferation. These results set the base for further studies on the mechanism of ECP, especially the regulatory role of ECP‐treated monocytes. Abstract : Although clinical benefits of ECP are already well described, the underlying mechanism of action of ECP, which is commonly used for the treatment of various T cell‐mediated disorders, is not yet fully understood. In this study, we established an in‐vitro ECP model focusing on ECP‐treated monocytes in co‐culture with CD4 + T cells as knowledge on the role of monocytes in ECP is particularly controversial and should be further investigated. We found that in‐vitro ECP treatment of monocytes (1) significantly induced proinflammatory T cell types dependent on cell‐contact, whereas anti‐inflammatory T cells were unaffected, (2) significantly reduced proliferation rates of co‐cultured T cells in a cell‐contact‐dependent manner partially due to PD‐L1–PD‐1 interactions as (3) blockade of this interaction by antibodies led to a slight but significant recovery of T cell proliferation.